Reprezentacija moškosti v popularnem rapu na primeru 50 Cent - Šadl, Zdenka (Teorija in praksa, 2007)
The presumption of this article originates in revitalization of hegemonic masculinity which defines femininity - the opposite pole negatively. Through analysis of audio-visual mediators between artist (i.e. 50 Cent) and audience it is established that representation of black masculinity is structured through traditional discourses of hegemonic masculinity, supplemented with elements of new masculinities: new man - narcissist and the vengeance man. Popular music and specially, popular rap is inscribed with sexism that is based upon pornographic aesthetics and expresses itself as celebration of masculinism (i.e. collection of attributes of man and/or system/ideology) and through presentation of women as sex objects.
Keywords: Popular music; Popularna glasba; Rap (Glasba); Rap (Music); Glasbeniki; Musicians; Seksizem; Sexism; Masculinity; Moškost; Hegemonism; Hegemonizem; United States of America; Združene države Amerike; rapping; rap; seksualnost; ZDA